The impact of gender and NASH on chronic kidney disease before and after liver transplantation. (21st November 2013) - Fussner, Lynn A.; Charlton, Michael R.; Heimbach, Julie K.; Fan, Chun; Dierkhising, Ross; Coss, Elizabeth; Watt, Kymberly D.
Abstract Background & Aims Chronic kidney disease (CKD) after liver transplant (LT) is associated with increased long‐term mortality. The impact of gender on CKD before and after LT is unknown. To further define risk factors and analyse gender differences in the incidence and progression of CKD after liver transplant. Methods Four hundred and fifty‐five consecutive adult primary solitary LT recipients were included. Iothalamate clearance tests performed over time were analysed. Results Mean age was 51.4 ± 10.4 years with 63% males. A percentage of 29.1% of females and 21.1% of males had a GFR<60 ml/min/1.73 m2 and 10.2% of females and 5.9% of males had GFR<30 ml/min/1.73 m2 prior to transplant. At 1 year, 52.6% of recipients tested (69.6% females, 43.0% males) had GFR<60 ml/min/1.73 m2 and 7.3% (11.6% females, 4.9% males) had GFR<30 ml/min/1.73 m2. Pre‐LT GFR<60 ml/min/1.73 m2 [OR 3.28, (1.76–6.10), P ≤ 0.001], female gender (OR 2.96, (1.72–5.10), P < 0.001) and age [OR 1.09, (1.05–1.12), P < 0.001] were independently predictive of stage ≥3 CKD at 1 year post‐LT. Female gender [OR 2.52, (1.25–4.71), P = 0.004], age [OR 1.05, (1.02–1.08), P = 0.003] and NASH [OR 2.95, (1.06–8.21), P = 0.039] were independently predictive of ≥stage 3 CKD at 5 years post‐LT. Pre‐LT diabetes was associated with stage 4 CKD at 5 years [OR 2.91, (1.33–6.36), P = 0.008] post‐LT. Conclusions In addition to age and pre‐LT CKD, female gender and NASH are independent predictors of ≥stage 3 CKD post‐LT. Gender‐based approaches to optimize modifiable risk factors are needed to improved post‐transplant renal function.